Immunosuppression with thalidomide, cyclosporine and diclofenac on survival of skin allograft - Chaves, Diva Novy Barbosa; Petroianu, Andy; Alberti, Luiz Ronaldo (Brazilian Journal of Transplantation, 2011)
Purpose: The authors report the case of a 21 years old female patient diagnosed with Ochoa´s Syndrome and chronic renal failure (CRF), who had a deceased donor kidney transplant and her post-transplantation evolution. Kidney transplant is a safe treatment for renal patients with Ochoa´s Syndrome that evolve to Chronic Renal Failure, despite the increased risk of UTI after transplantation. The vesical magnification with or without external continent urinary diversion added to the vesicle intermittent catheterization should be recommended to prevent damage to the renal graft.